Recent advances in understanding Crimean–Congo hemorrhagic fever virus - Hawman, David W. (F1000Res, 2018)
Crimean-Congo hemorrhagic fever virus (CCHFV) is a widely distributed hemorrhagic fever virus and the cause of hemorrhagic disease in Africa, Southern and Eastern Europe, the Middle East, India and Asia. Recent emergence of CCHFV into Spain indicates that the geographic range of this virus is expanding and the presence of its tick vector in several countries without reported disease suggest that CCHFV will continue to spread. Research into CCHFV was historically limited by a lack of suitable animal models and tools to study viral pathogenesis. However, in the past few years the toolset for studying CCHFV has expanded with small animal and non-human primate models for CCHFV being developed along with a reverse genetics system that allows for investigation of viral determinants of disease. These tools have been utilized to understand how CCHFV antagonizes host restriction factors and to develop novel vaccine candidates that may help limit the substantial morbidity and mortality in humans caused by CCHFV.